MP08: What's the plan?: Improving ED patient discharge communication through patient-centred discharge handouts. (15th May 2017) - Hall, J.N.; Graham, J.P.; McGowan, M.; Cheng, A.H.
Abstract : Introduction: Discharge from the Emergency Department (ED) is a high-risk period for communication failures. Clear verbal and written discharge instructions at patient-level health literacy are fundamental to a safe discharge process. As part of a hospital-wide quality initiative to measure and improve discharge processes, and in response to patient feedback, the St. Michael's Hospital ED and patient advisors co-designed and implemented patient-centred discharge handouts.Methods: The design and implementation of discharge handouts was based on a collaborative and iterative approach, including stakeholder engagement and patient co-design. Discharge topics were based on the 10 most common historical ED diagnoses. ED patient advisors and the hospital's plain language review team co-designed and edited materials for readability and comprehension. Process mapping of ED workflow identified opportunities for interventions. Multidisciplinary ED stakeholders co-led implementation, including staff education, training and huddles for feedback. Patient telephone surveys to every 25 th patient presenting to the ED meeting the study inclusion criteria (16 years of age or older, directly discharged from the ED, speaks English, has a valid telephone number, and has capacity to consent) were conducted both pre- (June-Sept 2016) and post- (Oct-Dec 2016) implementation.Results: Stakeholder engagement and co-design took place over 10 months. Education was provided across one MD staff meeting, four RN inservices, and at monthly learner orientation. 44846 patients presented to the ED and 25600 met the study inclusion criteria. 935 surveys (response rate=97%; declined n=30) were completed to date. Pre-implementation (n=467), 9.2% (n=43) of patients received printed discharge materials and 71% (n=330) understood symptoms to look for after leaving the ED. Post-implementation (n=468), 44% (n=207) of patients received printed discharge materials with 97% (n=200) finding the handouts helpful and 82% (n=385) understanding symptoms to look for after leaving the ED.Conclusion: Through the introduction of patient co-designed and patient-centred discharge handouts, we have found a marked improvement in patient understanding, and consequently safer discharge practices. Future efforts will focus on optimizing discharge communication, both verbal and written, tailored to individual patient preferences.